The influence of multiple trials and computer-mediated communication on collaborative and individual semantic recall. - Hinds, Joanne M.; Payne, Stephen J. (Memory, 2018)
Collaborative inhibition is a phenomenon where collaborating groups experience a decrement in recall when interacting with others. Despite this, collaboration has been found to improve subsequent individual recall. We explore these effects in semantic recall, which is seldom studied in collaborative retrieval. We also examine “parallel CMC”, a synchronous form of computer-mediated communication that has previously been found to improve collaborative recall [Hinds, J. M., & Payne, S. J. (2016). Collaborative inhibition and semantic recall: Improving collaboration through computer-mediated communication.Applied Cognitive Psychology,30(4), 554–565]. Sixty three triads completed a semantic recall task, which involved generating words beginning with “PO” or “HE” across three recall trials, in one of three retrieval conditions: Individual–Individual–Individual (III), Face-to-face–Face-to-Face–Individual (FFI) and Parallel–Parallel–Individual (PPI). Collaborative inhibition was present across both collaborative conditions. Individual recall in Recall 3 was higher when participants had previously collaborated in comparison to recalling three times individually. There was no difference between face-to-face and parallel CMC recall, however subsidiary analyses of instance repetitions and subjective organisation highlighted differences in group members' approaches to recall in terms of organisation and attention to others' contributions. We discuss the implications of these findings in relation to retrieval strategy disruption.